The El Nino–Southern Oscillation (ENSO) Modoki signal in the stratosphere - Zubiaurre, I. (I. Zubiaurre) (authoraut); Calvo Fernandez, Natalia (Natalia Calvo Fernandez) (authoraut) (Journal of Geophysical Research: Atmospheres)
El Nino-Southern Oscillation (ENSO) is known to be the largest source of interannual variability in the tropical troposphere. However, the variability in the tropical Pacific since 1979 seems to be associated not only with "canonical" ENSO events but also with a variation thereof known as ENSO Modoki, which is characterized by warm anomalies in the central Pacific, west from those occurring during a typical ENSO. This works analyzes the signal of ENSO Modoki in the stratosphere and compares it to canonical ENSO by using the chemistry-climate Whole Atmosphere Community Climate Model (WACCM3.5). The results reveal a significant warming in the Southern Hemisphere polar stratosphere during boreal winter months, which propagates downward in early spring; this is absent during canonical warm ENSO events. On the other hand, in the Northern Hemisphere stratosphere, the anomalous warming typical of canonical El Nino episodes during boreal winter is not statistically significant during El Nino Modoki events. These differences are related in WACCM3.5 to changes in tropical convection and tropospheric teleconnections associated with each type of event. In particular, an enhancement and westward displacement of the anomalous convective area during El Nino Modoki episodes is related to an intensification of the Pacific South American teleconnection pattern and a weakening of the Aleutian Low. During cold ENSO Modoki events a significant anomalous cooling is present in the model simulations.